A review on the development of visible light-responsive WO3-based photocatalysts for environmental applications - Murillo Sierra, Juan Camilo; Hernández Ramírez, Aracely; Hinojosa Reyes, Laura; Guzmán Mar, Jorge Luis (Elsevier, 2021)
The use of semiconductor photocatalysis is a promising, green, and sustainable technology to address solar energy conversion and environmental remediation issues. Among photocatalytically active semiconductors, considerable attention has been given to the visible-light active tungsten oxide (WO3, Eg value ≈ 2.7–3.1 eV). This semiconductor has several advantages: strong absorption in the visible spectrum range, stability in acidic and oxidative conditions, low cost, and low toxicity. However, WO3 presents fast recombination of charge carriers’ and exhibits low photocatalytic activity for reduction reactions due to its conduction band potential (+0.5 V versus NHE). Many strategies have been applied to enhance photocatalytic activity and solar energy utilization of WO3 by modifying the energy band position and reducing the charge carrier recombination. In this review, several approaches, such as designing with exposed facets and specific morphologies, doping with transition metals and non-metals, deposition of noble metals, and heterojunction construction, are summarized.